Demographic Effect on Switching Behaviour among Bank Customers in Ghana - Owusu Okyireh, Rexford; Kyei, Leonard; Tandoh and Nathaniel Mills, Dorcas (British Journal of Marketing Studies, 2017)
The issues that confront banks in their quest to offer superior value are as a result of effective segmentation and this presents marketers with a huge responsibility of providing the right products for customers to be delighted. However, the characteristics of customers are not the same; hence; expectations also differ in the same regard. This makes it paramount to understand the demographic variables such as age, income and education and how these variables impact a customers’ likelihood to switch. The study utilized a cross-sectional survey of 987 bank customers and a convenience sampling technique was employed. The data was analysed with Cross-tabulation and Chi-square. The study concludes that age, income and education are significant to the tendency for customers to switch banks.